Promoting Navigation Health Literacy at the Intersection of Schools and Communities. Development of the Game-Based Intervention Nebolus - Dadaczynski, Kevin; Krah, Verena; Frank, Demian; Zügel-Hintz, Elisabeth; Pöhlmann, Fabrice (Frontiers in Public Health, 2021)
Emerging empirical evidence indicates a limited health literacy for a substantial proportion of children and adolescents. Although it is generally agreed upon promoting health literacy as early as possible in the lifespan, there is a lack of interventions addressing children and adolescents and their primary living environments. This article describes the development of Nebolus, a game-based intervention aiming to promote navigation health literacy at the intersection of schools and communities. Its intervention foundation lies in a socio-ecological understanding of health as well as in the Entertainment Education approach. Following an extensive literature search on health-related location-based games, a co-creation process was initiated that involved adolescents, community stakeholders, and design/IT professionals in all phases of the intervention development. The final Nebolus intervention includes three core activities: (1) a Nebolus rally app for adolescents aged 12 to 16 years, (2) an online planning tool allowing local health service providers/professionals to set up own Nebolus rallies, and (3) accompanying teaching material on health literacy in the school setting to be used before and after the Nebolus rallies. This article provides an overview of the intervention layout and discusses strengths and challenges of its development and implementation.